STUDI KEBUTUHAN PERALATAN DAN BAHAN BAKAR PADA PEKERJAAN PEMBANGUNAN JALAN - SETIYONO, PUJO (KURVA S JURNAL MAHASISWA, 2014)
Heavy equipment is a tool used to assist humans in performing the construction work of a building structure. Project road construction work which consists of 5 packets, use the type tool type Excavator PC 200, PS 125 Dump Truck, Motor Grader GD511A type-1 and type Vibrator JV 100A-2. The subjects in this study is to determine the selection of heavy equipment to be used, calculate the value of productivity and the number of devices used, as well as calculate the required amount of fuel oil (BBM) of diesel for each tool.The highest yield of the value of productivity and the number of tools used and the fuel contained in the package 4 with a path length of 10.6 Km. Excavator type PC 200 (Productivity = 1374.52 m3/ day, number of units = 2 units, fuel = 5540.04 liters). Dump Truck 125 PS (Productivity = 761.53 m3/ day, number of units = 11 units, fuel = 1281.44 liters). Motor Grader GD511A type-1 (Productivity = 8400 m3/ day, number of units = 1 unit, fuel = 657.3 liters). Vibrator type JV 100A-2 (Productivity = 846.57 m3/ day, number of units = 1 unit, fuel = 1170.87 liters).